(untitled) - Reinking, James A. (Upper Saddle River, N.J., 2005)
This best-selling text combines three books-a rhetoric, a research guide, and reader-into one convenient and flexible teaching tool while offering students an exceptional value. Also available in an alternate versionwith a Handbook section.
Keywords: English language,English language,Ngôn ngữ Anh,Ngôn ngữ Anh; Rhetoric,Grammar,Tu từ,Ngữ pháp